Evaluating Health-Related Quality of Life (HRQoL) in Iraqi Adult and Pediatric Patients with Beta-Thalassemia Major Using Two Different Iron Chelation Therapies - Shawkat, Ali Jalal; H. Jwaid, Ahmed; M. Awad, Ghada (Iraqi Journal of Pharmaceutical Sciences, 2019)